Ce-Doped Smart Adsorbents with Photoresponsive Molecular Switches for Selective Adsorption and Efficient Desorption. (May 2020) - Tan, Peng; Jiang, Yao; Qi, Shi-Chao; Gao, Xia-Jun; Liu, Xiao-Qin; Sun, Lin-Bing
Abstract: Achieving efficient adsorption and desorption processes by controllably tuning the properties of adsorbents at different technical stages is extremely attractive. However, it is difficult for traditional adsorbents to reach the target because of their fixed active sites. Herein, we report on the fabrication of a smart adsorbent, which was achieved by introducing photoresponsive azobenzene derivatives with cis / trans isomers to Ce-doped mesoporous silica. These photoresponsive groups serve as "molecular switches" by sheltering and exposing active sites, leading to efficient adsorption and desorption. Ce is also doped to provide additional active sites in order to enhance the adsorption performance. The results show that the cis isomers effectively shelter the active sites, leading to the selective adsorption of methylene blue (MB) over brilliant blue (BB), while the trans isomers completely expose the active sites, resulting in the convenient release of the adsorbates. Both selective adsorption and efficient desorption can be realized controllably by these smart adsorbents through photostimulation. Moreover, the performance of the obtained materials is well maintained after five cycles.